Validity of Instruments for Assessing Numeration, Digital, and Cultural Literacy Skills for Class VII Junior High School Students - Indah Suciati; Mohammad Jamhari; Ratman Ratman; Astija Astija (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The research aims to produce an instrument for assessing class VII students' numeracy, digital, and cultural literacy skills. Method: This study employed a research and development (R&D) approach using the 4-D model, consisting of the Define, Design, Develop, and Disseminate stages, with the research conducted up to the Develop stage due to time and cost constraints. The method involved expert validation of the numeracy, digital, and cultural literacy assessment instruments using validation sheets that evaluated content, construction, and language, with expert feedback used to refine the instruments. Results: The research shows that the numeracy, digital, and cultural literacy assessment instruments are valid and reliable, with validity scores for the three instruments in the very valid category. This indicates that the numeracy, digital, and cultural literacy assessment instruments can be used to measure students' abilities in these literacies. Novelty: These findings imply that valid and reliable assessment instruments can strengthen the implementation of competency-based assessment by providing teachers with practical tools to measure numeracy, digital, and cultural literacy skills. Consequently, the instruments can facilitate evidence-based learning evaluation and support educational policies aimed at developing students' 21st-century competencies.